Protoplast production and isolation from Etlingera elatior - Jessé Marques da Silva Júnior (Acta Scientiarum. Agronomy, 2012)
The technique of hybridization using plant protoplasts is widely used in plant breeding programs. The purpose of our study is to further characterize the process of protoplast isolation from the ornamental species Etlingera elatior (Jack) R. M. Smith. Protoplasts were isolated from different tissues: in vitro leaves, in vitro pseudostem, and leaves from plants cultivated hydroponically. We tested six enzymatic combinations, four incubation time periods, the rotary system (40 rpm) or steady in the dark, and three concentrations of mannitol (0.5, 0.6 and 0.7 M). The diameter and viability of obtained protoplasts were evaluated. The best source of explants used for protoplast isolation was the in vitro leaves, which yielded 22x105 protoplasts g-1 of fresh matter. The optimal incubation period was 15 hours. The in vitro leaves presented a greater viability (96%) and larger protoplasts (36.7 µm diameter). Greater yields were obtained using a rotatory system with protoplasts incubated in the dark. The best enzymatic combination was 3% Cellulase “Onozuca” R-10 + 2% Meicelase + 1% Driselase + 1% Dextran + 5 mM MES, followed by the addition of 0.6 M mannitol.Keywords: FDA, ornamental plant, enzymatic combinations, incubation period